EFFECTS OF SALARY LOANS TO FINANCIAL WELLNESS OF PANACAN NATIONAL HIGH SCHOOL TEACHERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The overall goal of this study is to look into the existing effects of salary loans on teachers' financial wellness at Panacan National High School. Teachers may be saved from their debts if the Department of Education implements institutional changes. This research followed a descriptive design and utilized online survey questionnaire as its method. Frequencies and percentages were computed to measures and examine the encountered problems of the respondent-teachers. The survey was conducted in Panacan National High School Teachers at Panacan, Narra, Palawan. Results shows that the financial capability of public-school teachers is far from what is desired and merely reflects the negative trend on financial capability nationally and all over the world. Contributing to this finding are the respondent-teachers’ deficient money management skills, low incidence of financial planning, and inadequate knowledge on basic financial concepts as reflected in their dismal performance in the financial literacy. Integrating financial education in the teacher education curriculum and in-service training of public-school teachers can be an effective means not only to enrich the academic training of future teachers, but also to empower them to secure a wealthier and prosperous future for themselves and for their family. While the current study provided server insights on the current level of financial capability of the public-school teachers in terms of its Financial Wellness. further research is necessary to validate these findings.